Neuromuscular Responses to Short-Duration Percussive Massage: Effects on Muscle Activation and Lower-Limb Explosive Power in University Teqball Athletes - Zainuddin, Erwin; Tritama, Anugrah Riski; Zetira, Zahra; Ilham, Zalikal; Arif, Muh (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2026)
The purpose of the study. Percussive massage therapy has emerged as a popular pre-exercise intervention; however, its acute effects on neuromuscular function in hybrid precision sports remain inadequately characterized. This study investigated the acute effects of a 10-minute percussive massage intervention on quadriceps and hamstring muscle activation and lower-limb extensor power in university Teqball athletes. Materials and methods. A single-blind randomized controlled pretest-posttest design was employed involving 20 Teqball athletes (16 males, 4 females; mean age 21.35 ± 1.89 years). Participants were randomly allocated to either a massage intervention group (n = 10) or a passive control group (n = 10). The intervention consisted of bilateral quadriceps and hamstring percussive massage (40–60 Hz, 10 minutes total). Primary outcomes included muscle activation of the vastus lateralis and biceps femoris measured via surface electromyography (sEMG; root mean square amplitude, μV), and lower-limb explosive power assessed through countermovement jump (CMJ) height. Data were analyzed using repeated-measures ANOVA with Bonferroni post-hoc corrections (α = 0.05). Results. Significant improvements were observed in the massage group for vastus lateralis activation (+28.4%, p = 0.002, Cohen’s d = 1.89), biceps femoris activation (+24.7%, p = 0.008, d = 1.67), and CMJ height (+12.6%, p = 0.001, d = 1.42). No significant changes were observed in the control group (all p > 0.05). Significant Time × Group interaction effects were identified for all outcome measures (all p < 0.01). Conclusions. A 10-minute percussive massage intervention significantly enhances neuromuscular activation and lower-limb explosive power in Teqball athletes, demonstrating large practical effect sizes. These findings support the integration of percussive massage as an effective, non-fatiguing pre-competition warm-up modality in hybrid precision sports.